2022
DOI: 10.1038/s41467-022-32107-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteotoxicity caused by perturbed protein complexes underlies hybrid incompatibility in yeast

Abstract: Dobzhansky–Muller incompatibilities represent a major driver of reproductive isolation between species. They are caused when interacting components encoded by alleles from different species cannot function properly when mixed. At incipient stages of speciation, complex incompatibilities involving multiple genetic loci with weak effects are frequently observed, but the underlying mechanisms remain elusive. Here we show perturbed proteostasis leading to compromised mitosis and meiosis in Saccharomyces cerevisiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 85 publications
0
0
0
Order By: Relevance
“…However, it is noteworthy that no hybrids were produced from one Bioethanol lineage strain. While we did not investigate the underlying reasons for this observation, we believe that certain genetic incompatibilities identified in interspecific hybridizations, particularly those related to mitochondrial and nuclear interactions, might account for the disparities in the mating rates of our hybrids (Blanckaert & Payseur, 2021; Lee et al, 2008; Moran et al, 2024; Swamy et al, 2022). Ploidy analysis revealed that rate mating led to a higher proportion of triploids hybrids.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is noteworthy that no hybrids were produced from one Bioethanol lineage strain. While we did not investigate the underlying reasons for this observation, we believe that certain genetic incompatibilities identified in interspecific hybridizations, particularly those related to mitochondrial and nuclear interactions, might account for the disparities in the mating rates of our hybrids (Blanckaert & Payseur, 2021; Lee et al, 2008; Moran et al, 2024; Swamy et al, 2022). Ploidy analysis revealed that rate mating led to a higher proportion of triploids hybrids.…”
Section: Discussionmentioning
confidence: 95%